HOLISTIC APPROACH TO THE CHILD IN PEDIATRIC INTENSIVE CARE - Danijela Prelogar; Matjana Koren Golja (The Society for Children with Metabolic Disorders, 2023)
The pediatric intensive care unit is a complex environment where children, their parents and healthcare professionals have personal experiences. Critically ill children may experience various discomforts during their stay; they are vulnerable and dependent on healthcare professionals to acknowledge their needs. Therefore, they should be approached from a holistic perspective, which improves the quality of care and increases the satisfaction of children's family and staff well-being.